Students’ Ability to Develop Critical Thinking Skills in English Essay Writing - Safitri, Ayu; Adani, Sukri (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
Critical thinking has an important role in writing to analyze information, construct robust arguments, and communicate ideas understandably and compellingly. This study aims to know students’ ability to develop critical thinking in essay writing. The method used in this study is descriptive qualitative reserch with 50 students as participants. The test was used as a technique of data collection. The result of the study indicated that students' ability to develop critical thinking in writing remains underdeveloped, only 2% of students were able to demonstrate a clear unity of ideas in their essays, reflecting a notable lack of critical thinking skills in articulating main concepts. Furthermore, 8% of students were able to present clear reasoning, underscoring the overall weakness in their critical thinking abilities. Additionally, only 6% of students showed proficiency in the organization component of their essays, indicating a substantial gap in their skills to structure and connect ideas effectively. These findings demonstrate that students' application of critical thinking abilities, particularly in essay writing, is still lacking. It is recommended the students should develop critical thinking to have good achievement in writing.